N Impact of school-based exercises on physical fitness outcomes among sedentary high school boys in Vinh city, Vietnam - Hung Manh Nguyen (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Sedentary lifestyles increasingly threaten the health of children and adolescents. The purpose of this study is to assess the impact of school-based exercises on the physical fitness outcomes among sedentary high school boys.